Monetary Valuation of Aircraft Noise - Jasper Dekkers; Willemijn van der Straaten (Tinbergen Institute, 2008)
In densely-populated countries and in particular in large metropolitan areas, the presence of so much human activity causes all sorts of negative externalities, for example traffic noise disturbance. These externalities call for corrective measures by the government. Economists have developed a number of procedures that provide reasonable estimates on the monetary value of some amenities and externalities. In this paper we develop a spatially-explicit hedonic pricing model for house prices in order to quantify the social cost of aircraft noise disturbance in monetary terms. While focusing on aircraft noise around Amsterdam airport in the urban fringe of the Amsterdam region, a key point in our analysis is that we account for background noise. We do this by taking multiple sources of traffic noise (i.e. road, railway and aircraft noise) into account simultaneously and by setting threshold values for all three sources of noise above which sound is generally experienced as nuisance. Based on our regression results we conclude that a higher noise level means ceteris paribus a lower house price. Air traffic has the largest price impact, followed by railway traffic and road traffic. These model outcomes can subsequently be used to estimate the marginal and total benefits of aircraft noise reduction in the studied area around Amsterdam airport. We find a marginal benefit of 1 dB noise reduction of 1,459 Euro per house, leading to a total benefit of 1 dB noise reduction of 574 million Euros.
Keywords: D62; Q53; R41; R48; 330; aircraft noise; GIS; hedonic price theory; noise reduction; valuation; Lärm; Flughafen; Hedonischer Preisindex; Lärmschutz; Amsterdam; Niederlande